Characteristics of thermal and momentum transport during the lifetime of Ural blocking highs. (10th July 2019) - Li, Yan; Lu, Yao; Wang, Chenghai
Abstract : Ural blocking (UB) event is an important large‐scale weather system dominating cold waves in East Asia. This paper investigates the thermal‐dynamical variation characteristics associated with UB evolution via 32 UB events in winter during 1979–2016. The results show that transport of stationary heat and momentum changes prominently from 3 and 6 days before and after UB establishment. Specifically, on 3 days prior to the UB event establishment, an apparent convergence of stationary heat flux ({ v*T* }), which can extend from lower‐middle troposphere to the tropopause, is observed at around 60°N in the Urals region. The diagnosis shows that the convergence of stationary heat flux weakens the meridional temperature gradient ( − ∂ T ∂ y ) and thermal wind, and thus the zonal westerly weakens. The convergence of ({ v*T* }) also support formation of the warm centre structure of UB event. Meanwhile, convergence of momentum flux reverses to be a divergence in the Urals region (60°N), which contributes to decrease of the zonal wind. The heat and momentum flux reduce the intensity of the westerly and are beneficial for the establishment of UB event. Along with UB event establishment, the convergence of stationary heat flux weakens, and the divergence of momentum flux strengthens, accompanying with decrease of wind speed at middle latitudes and maintaining of the UB event. Six days later, the convergence of stationary heat flux disappears and divergence of momentum flux changes to be convergence and then the UB event collapses. Further analyses also suggest that the polar front jet (PFJ) enhances (weakens) coincidently before (after) the establishment of UB, which is attributed to the strengthening (weakening) of the convergence of ({ u*v* }) around 70°N. Abstract : The diagnosis shows that the convergence of stationary heat flux weakens the meridional temperature gradient ( − ∂ T ∂ y ) and thermal wind and benefits to the formation of the warm centre structure of UB event. Meanwhile, convergence of momentum flux reverses to be a divergence in the Urals region (60°N), which contributes to decrease of the zonal winds. The heat and momentum flux reduce the intensity of the westerly and are beneficial for the establishment of UB event. Along with UB event establishment, the convergence of stationary heat flux weakens and divergence of momentum flux strengthens, accompanying with decrease of wind speed at middle latitudes and maintaining of the UB event. Variation of GPH (unit: gpm) and ( − ∂ ∂ p ∂ ∂ y v * T * ) (unit: m s −1 K latitude −1 hPa −1 ·1000) (Figure 6a), ({ u * v * }) (unit: m 2 s −2 ) (Figure 6b) at 500 hPa during the lifetime of UB event.